2007
DOI: 10.1002/app.26722
|View full text |Cite
|
Sign up to set email alerts
|

A new method to visualize and characterize the pore structure of TENCEL® (Lyocell) and other man‐made cellulosic fibres using a fluorescent dye molecular probe

Abstract: ABSTRACT:The internal porous structures of the manmade cellulosic fibers Lyocell (TENCEL 1 ), Modal, and Viscose fibers were visualized by applying fluorescence microscopy on fiber cross sections. The fiber pore structure was probed by the optical brightener Uvitex BHT, and the dye penetration depth was measured. The main differences in the pore structures of these three fiber types could be visualized. Only TENCEL shows a significant difference between dried and never-dried fibers. A fiber structure model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The lyocell fiber used here was manufactured with a regenerating bath containing N‐Methylmorpholine N‐oxide (NMMO) and water. Abu‐Rous and coworkers observed the cross section of a similar type lyocell fiber using transmission electron microscopy, where the fiber cross section contained a compact core, a porous middle zone, and a semipermeable fiber skin. The cellulose dissolution and the ultimate mechanical properties of the lyocell ACCs were solely dependent on the structure of these lyocell fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The lyocell fiber used here was manufactured with a regenerating bath containing N‐Methylmorpholine N‐oxide (NMMO) and water. Abu‐Rous and coworkers observed the cross section of a similar type lyocell fiber using transmission electron microscopy, where the fiber cross section contained a compact core, a porous middle zone, and a semipermeable fiber skin. The cellulose dissolution and the ultimate mechanical properties of the lyocell ACCs were solely dependent on the structure of these lyocell fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Only few of the recorded spectra (like Tencel 1 in Fig. 4) were similar to pure cellulose-based fiber as lyocell ought to be [30][31][32]. Most of the spectra contained in addition to lyocell bands (~ 3500, ~ 3460, ~ 1130 cm −1 ) also N-H stretching absorbances (~ 3330 cm −1 ) and amide C=O stretching bands at ~ 1660 cm −1 , better seen in Fig.…”
Section: Reflectance Spectra Of Different Single-component Textile Fimentioning
confidence: 99%
“…Pores or voids are present in these fibres and were also shown to be elongated in the fibre direction [7,8]. Abu-Rous et al [9,10] showed that regenerated cellulose fibres contain only nanopores in the core of the fibre and a very porous skin layer. The structure of regenerated cellulose fibres is dependant of various parameters as the initial cellulose solution, the composition and the temperature of the aqueous regeneration bath and the spinning conditions [11,12].…”
Section: Introductionmentioning
confidence: 99%